Teacher Instructional Leadership A Site Study at SMK Negeri 2Purbalingga - Sugiantoro, Teguh (2011)
This study aims to describe (1) the characteristic of teacher's leadership in designing of learning room at SMK Negeri 2 Purbalingga; (2) the characteristic of the teacher's leadership in the use of instructional method at SMK Negeri 2 Purbalingga; (3) the characteristic of the teacher's leadership in the use of instructional media at SMK Negeri 2 Purbalingga. This study is a qualitative study. This research was conducted at SMK Negeri 2 Purbalingga with the informants, namely the principal, teacher, and students. The method to collect data used in-depth interview, observation, and documentation. Data analysis technique used was an analysis technique arranged in a site. Data validity used triangulation. The results of the study show: (1) Teacher's leadership in designing of learning room is focused on the effort to give a comfortable condition in teaching and learning activity. Teacher's leadership in designing the learning room consider the method and leaning model, material, time efficiency, and learning place. The principles used to design the learning room are the efficiency, effectiveness, and comfortable. Teacher's leadership in designing the learning room is not centralistic due to the cooperative learning give a freedom to students to make their own group; (2) Teacher's leadership in the use of instructional method is that teacher can identify the students' potential, create the curiosity, and students' participation, guide students to find the true fact. Teacher's leadership in using the cooperative learning method is that teacher acts as the facilitator and supervisor and dividing the tasks of each learning group. Teacher's leadership in using the learning method is that teacher can help to develop the students' ability, sensitive to the situation, being empathetic, guide students, support students to be able to be developed. Teachers act as evaluator of the implementation of learning and use of learning methods; (3) One of the instructional media characteristics used is the instructional media based e-learning. Teacher's leadership in using the e-learning instructional media is realized in teacher's activity to make the teaching preparation suitable with the e-learning concept and create instructional media based e-learning. The instructional media based e-learning delivered is in soft file in the form of word, power point, completed with picture, graph, or chart. Teacher's leadership in using the instructional media is independent, where teacher has an initiative with creating personal blog and utilizing it to deliver learning material.